ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PELAKU USAHA INFORMAL DI KELURAHAN JIMBARAN, KABUPATEN BADUNG - Putra, I Kadek Cahya Wirakusuma; Dewi, Ni Putu Martini (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023DO - 10.24843/EEB.2023.v12.i10.p12, 2023)
This study aims to analyze the effect of capital, working hours, and length of business on the income of informal business actors in Jimbaran Village. The number of samples in this study were 43 respondents. This study uses primary data obtained through observation, structured interviews, and in-depth interviews. The data were analyzed using multiple linear regression analysis techniques. The results showed that the capital, working hours, and length of business simultaneously had a significant effect on the income of informal business actors in Jimbaran Village. Capital and length of business partially have a positive and significant effect on the income of informal business actors. Meanwhile, working hours partially have no significant effect on the income of informal business actors. This indicates that if working hours increase or decrease, it cannot affect the income of informal business actors, assuming other variables are constant. Business actors can also adjust working hours taking into account current conditions in the field, such as opening full-day on weekends so that customers who are busy working on weekdays can use the services on their days off .